2018
DOI: 10.1016/j.ejca.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Olaratumab in soft tissue sarcoma – Current status and future perspectives

Abstract: Recent randomised phase II trial data have indicated that the addition of olaratumab, a novel monoclonal antibody against platelet-derived growth factor receptor alpha (PDGFRα), to doxorubicin confers an unprecedented improvement in overall survival to patients with anthracycline-naïve advanced soft tissue sarcoma. However, this result was disproportionate with progression-free survival and response rate, and consequently there are unanswered questions regarding the precise mechanism of action of olaratumab. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…The safety and tolerability findings from this study are consistent with those from previous studies of olaratumab plus doxorubicin [1,12] by pre-existing IgE antibodies for alpha-Gal, that are likely recognizing alpha-Gal containing glycosylation sites of the Fab region of olaratumab [29].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The safety and tolerability findings from this study are consistent with those from previous studies of olaratumab plus doxorubicin [1,12] by pre-existing IgE antibodies for alpha-Gal, that are likely recognizing alpha-Gal containing glycosylation sites of the Fab region of olaratumab [29].…”
Section: Discussionsupporting
confidence: 89%
“…Soft tissue sarcomas (STS) are a group of rare and heterogeneous mesenchymal tumors, comprising approximately 1% of adult cancers [1]. The management of STS remains challenging, partly due to a lack of effective systemic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…While the combination of olaratumab and doxorubicin might not be beneficial in all STS cases, certain subgroups might well benefit from the treatment. Unfortunately, different efforts could not establish PDGFRA as a reliable marker, as it is heterogeneously expressed in the stromal component of the tumour microenvironment and the tumour itself [24]. For instance, the ANNOUNCE trial showed an improved OS in patients negative for PDGFRA compared to those with relevant PDGFRA expression [5].…”
Section: 7%mentioning
confidence: 99%
“…Jedná se o lidskou monoklonální proti látku třídy IgG1, která specificky a s vyso kou afinitou rozeznává extracelulární li gandvazebnou doménu PDGFRα, čímž zabraňuje vazbě ligandu a aktivaci re ceptoru. V in vitro a in vivo podmínkách olaratumab signifikantně inhiboval růst řady sarkomových buněčných linií [24] a překvapivě dobrého výsledku bylo dosaženo v kombinované klinické stu dii fáze I/ II (studie JGDG), u které kombi nace olaratumabu a doxorubicinu prak ticky zdvojnásobila celkovou dobu přežití oproti monoterapii doxorubicinem u sou boru pa cientů s pokročilými sarkomy měkkých tkání [25]. Na konferenci CTOS 2018 byla představena návazná studie (přednáška dr. S. Bauer), u které byl kombi nován olaratumab s kombinační chemote rapií doxorubicinem a ifosfamidem.…”
Section: Ewsr1 -Ets (Fli1 Erg)unclassified
“…Lze rovněž doufat, že tato nová kombinace pomůže osvětlit ně kte ré z ne zcela jednoznačně interpre tovatelných závěrů studie JGDG, např. ne zcela snadno vysvětlitelný nesoulad mezi jen poměrně skromným zvýšením doby do progrese a poměrně razantním zvýšením celkového přežití, jakož i ne možnost prokázat jakýkoliv vztah mezi expresí PDGFRα v nádoru a léčebnou odpovědí [25].…”
Section: Prognostické Nomogramy Sarkomů Měkkých Tkáníunclassified